The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1111/faf.12711
|View full text |Cite
|
Sign up to set email alerts
|

Projecting species distributions using fishery‐dependent data

Abstract: Many marine species are shifting their distributions in response to changing ocean conditions, posing significant challenges and risks for fisheries management. Species distribution models (SDMs) are used to project future species distributions in the face of a changing climate. Information to fit SDMs generally comes from two main sources: fishery‐independent (scientific surveys) and fishery‐dependent (commercial catch) data. A concern with fishery‐dependent data is that fishing locations are not independent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 102 publications
0
22
1
Order By: Relevance
“…In contrast, the fishery‐independent models exhibited generally lower evaluation metrics but were more broadly robust in their predictive performance and ecological realism, suggesting they may more accurately represent the realized environmental niche and geographic distribution of blue sharks beyond the footprint of the fishery. This distinction regarding the relative strengths of different data types may have even greater relevance for model projections to understand how species' distributions and their interactions with fisheries may shift under climate change (Karp et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, the fishery‐independent models exhibited generally lower evaluation metrics but were more broadly robust in their predictive performance and ecological realism, suggesting they may more accurately represent the realized environmental niche and geographic distribution of blue sharks beyond the footprint of the fishery. This distinction regarding the relative strengths of different data types may have even greater relevance for model projections to understand how species' distributions and their interactions with fisheries may shift under climate change (Karp et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…While previous studies have suggested that fisherydependent and fishery-independent datasets can lead to consistent estimates of species' habitats (Karp et al, 2023;Pennino et al, 2016) F I G U R E 6 Proportion of presences (sensitivity, a) and "true" absences from the observer data (specificity, b) correctly predicted by each selected model (Table 4) and dataset combination. Model predictions were considered "correct" when predicted suitability was greater than the 75% quantile for presence observations and less than the 25% quantile for absences in the observer data.…”
Section: Leveraging Diverse Data Typesmentioning
confidence: 97%
“…Finally, there are continuity issues in scientific data collection in relation to a changing world. For example, in the context of climate change, scientific surveys that are standardized to allow for time-series development of relative changes in fish stock populations may miss important changes in stock dynamics (Karp et al, 2022). Here, fishers'…”
Section: Uniqueness Of Knowledgementioning
confidence: 99%
“…What makes 'anecdotal' information considered to be less true useful for monitoring change is not necessarily that it is less true, but that it is regarded as not 'systematic' (Wilson, 2009). For example, stock assessment science tends to be based on large spatial scale units, discrete sampling techniques, and standardized sampling protocols, whereas experiential knowledge is often more localized and is based on different and often variable temporal scales and continuous sampling practices and technologies (Perry and Ommer, 2003;Wilson, 2009;Karp et al, 2022). These are some of the reasons why experiential knowledge is often considered unusable in fish stock or ecological assessment models; particularly those that are already data-rich (Mackinson and Nøttestad, 1998).…”
Section: Issue 2: Uniqueness Of Fishers' Knowledgementioning
confidence: 99%
“…Given the multitude benefits of using fishers' knowledge to inform policy, it begs the question why it's underutilized? For catch data, there is the issue of bias in samples for density estimates, as catch logs exclusively record instances of fishing activity, neglecting areas not targeted by fishers, which biases predictions of species distributions (Karp et al, 2022). Also, given the unsystematic way much of fishers' knowledge is handled, it is often neglected (Hind, 2015).…”
Section: Introductionmentioning
confidence: 99%